Chỉ tiêu thống kê về công bố khoa học và công nghệ - Lê, Xuân Định (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Presents some methods to define statistical indicators on scientific and technological publication such as bibliometrics, impact coefficient, citation index; describes content, calculating method and expression way of 3 statistical indicators on scientific and technological publication in Vietnam: number of Vietnamese scientific articles published domestically and abroad; number of cited Vietnamese scientific articles published abroad; and number of awarded national and international scientific and technological prize; number of persons awarded with these prizes